1998
DOI: 10.2116/analsci.14.269
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Writing Ink Dyestuffs by TLC and FT-IR and Its Application to Forensic Science

Abstract: Various writing implements have often been used at crime scenes in Japan. One of the purposes for the examination of writing ink is to specify writing implements. A number of papers have been published regarding techniques for forensic examinations, including visible spectrophotometry 1,2 , thin-layer chromatography (TLC) 1-4 , X-ray microanalysis 1 , microspectrophotometry 3,5 , high-performance liquid chromatography (HPLC) 6 , gel electrophoresis 7 and capillary zone electrophoresis. 8,9 TLC is the simplest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 10 publications
0
24
0
Order By: Relevance
“…For blue inks, 90% or more of the possible pairs in each group could be discriminated. Other studies on the forensic analysis of inks reported DPs of 0.9 (14) and 0.99 (6). Only in the case of group 2 of the black inks, a much lower DP was observed.…”
Section: Resultsmentioning
confidence: 96%
“…For blue inks, 90% or more of the possible pairs in each group could be discriminated. Other studies on the forensic analysis of inks reported DPs of 0.9 (14) and 0.99 (6). Only in the case of group 2 of the black inks, a much lower DP was observed.…”
Section: Resultsmentioning
confidence: 96%
“…In particular, the chromatographic separation of ballpoint pen ink into its constituent component dyes has proved a highly productive method, not only for the comparison of inks but also for the matching of an ink to a database of chromatograms. Thin layer chromatography (TLC) is widely used as it is rapid and requires no sophisticated instrumentation [1,5]. Its limited resolution and difficulties with quantification have led to the application of high performance liquid chromatography (HPLC) [4] and, more recently, capillary electrophoresis (CE) [6] to ink analysis.…”
Section: Introductionmentioning
confidence: 99%
“…These components can be assayed by a number of analytical chemistry techniques including high performance liquid chromatography (HPLC) [1][2][3] and infrared spectroscopy (IR) [4,5]. This work evaluated and compared these two techniques for a variety of blue ballpoint pens.…”
Section: Introductionmentioning
confidence: 99%